1995
DOI: 10.1111/j.1365-3148.1995.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre assessment of the specificity of ten anti‐HBc screening tests

Abstract: Samples from 1828 donations were screened for anti-HBc at seven sites in the UK using kits supplied by 10 manufacturers. Only 10 (0.55%) donations were considered to have true anti-HBc reactivity and these were detected by all 10 kits. Additional markers of HBV infection were found in nine of these 10 donations. Additional reactives were found by all kits, the number ranging from 1 to 43. In the four more specific kits, the 10 true reactives were clearly distinguished from the 'false reactives' by the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…These 6 donors had to be temporarily deferred. Fortunately, this number of false-positive results is lower than expected from data previously reported by Hughes et al [20] and certainly is due to improved and more specific test systems. In this respect, both tests showed a comparably high specificity which is supposed to be sufficient for the screening of a low-prevalence population.…”
Section: Discussioncontrasting
confidence: 51%
“…These 6 donors had to be temporarily deferred. Fortunately, this number of false-positive results is lower than expected from data previously reported by Hughes et al [20] and certainly is due to improved and more specific test systems. In this respect, both tests showed a comparably high specificity which is supposed to be sufficient for the screening of a low-prevalence population.…”
Section: Discussioncontrasting
confidence: 51%
“…Testing for anti-HBc contributed at that time to the reduction in the number of post-transfusion hepatitis B cases in these countries 39,40. On the other hand, in HBV low-prevalence countries, a large proportion of the anti-HBc reactive blood donations may be false reactive, due to the lack of specificity of the available assays 4143. The reason for this lies within the original development of anti-HBc tests.…”
Section: Anti-hbc Testingmentioning
confidence: 99%
“…Gomes et al (1996) demonstrated that samples presenting isolated anti-HBc as well as anti-HBc/anti-HBs contain HBV-DNA at a very low concentration, close to the limit of detection. Moreover, the occurrence of false anti-HBc positivity was reported by Douglas et al (1993) and Hughes et al (1995).…”
mentioning
confidence: 98%